How to run biotransformations⿿At the optimal temperature control or isothermally? Mathematical assessment. (August 2016) - Grubecki, Ireneusz
Graphical abstract: Highlights: ⿢ A simple biotransformation with deactivation of native enzyme was considered. ⿢ Isothermal conditions and optimal temperature control (OTC) were analyzed. ⿢ The presence of the temperature constraints were taken into account. ⿢ The high values of energy activation quotient justify application of OTC. ⿢ The application of OTC is profitable at the low values of final enzyme activity. Abstract: The optimization of batch biotransformations has attracted attention in recent years because, in the face of growing competition, it is a natural choice for reducing production costs and improving product quality. However, in many cases the effects achieved as a result of optimization may be less valuable in comparison to those obtained when the process is carried out in possibly the simplest way. Hence, in the present paper a mathematical analysis was proposed to assess if application of the optimal temperature control (OTC) in biotransformations with deactivation of native enzyme is justified. At the same time a simple biotransformation process accomplished in the presence of a native enzyme undergoing deactivation independent of or dependent on substrate concentration was considered. The estimation has been done on the basis of the indicator expressed by a quotient of the process duration under time-optimal temperature control and that for isothermal conditions (IC). It has been found that application of the OTC is justified when the biotransformation process is characterized by a high value of the quotient of activation energies referring to enzyme deactivation and for enzymatic reaction which is running up to attain a high conversion and low final enzyme activity. Moreover, application of the OTC in biotransformations with a parallel enzyme deactivation enables significant reduction of process duration in comparison to those with deactivation independent of substrate concentration. Framework proposed here can be helpful for evaluation of economic aspects of the optimally controlled process.